2024
DOI: 10.3390/ijms25031622
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Expression and Purification Protocol for SpCas9 Nuclease and Evaluation of Different Delivery Methods of Ribonucleoprotein

Konstantin Evmenov,
Nikolay Pustogarov,
Dmitri Panteleev
et al.

Abstract: The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-Cas9 system is a revolutionary tool for precise genome editing across various cell types. Ribonucleoproteins (RNPs), encompassing the Cas9 protein and guide RNA (gRNA), have emerged as a promising technique due to their increased specificity and reduced off-target effects. This method eliminates the need for plasmid DNA introduction, thereby preventing potential integration of foreign DNA into the target cell genome. Given the requirement f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…As per existing literature, optimized E. coli strains, such as Rosetta2, have been commonly chosen for SpCas9-His protein expression; however, the reported studies vary significantly in expression conditions, displaying concerns about productivity and scalability. Previous research employed complex culture media, low induction temperatures, and extended induction times, often associated with challenges and low SpCas9-His protein expression levels [ 21 , 27 , 28 , 29 ]. Moreover, these studies lacked stringent control of bacterial growth in bioreactors.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As per existing literature, optimized E. coli strains, such as Rosetta2, have been commonly chosen for SpCas9-His protein expression; however, the reported studies vary significantly in expression conditions, displaying concerns about productivity and scalability. Previous research employed complex culture media, low induction temperatures, and extended induction times, often associated with challenges and low SpCas9-His protein expression levels [ 21 , 27 , 28 , 29 ]. Moreover, these studies lacked stringent control of bacterial growth in bioreactors.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…In this study, SpCas9-His protein expression was initially assessed using the temperature and IPTG concentration conditions (0.5 mM IPTG at 18 °C overnight) from the existing literature [ 21 ]. Consequently, we conducted small-scale expression experiments (in shake flasks with 50 mL of LB media) of SpCas9-His protein with various bacterial strains, including BL21(DE3)-pLysS, BL21(DE3)-Star, Rosetta2, and BL21(DE3), and found that BL21(DE3)-pLysS exhibited superior expression compared to others.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delivery of the CRISPR/Cas9 system into cells is a critical factor in gene editing. The RNP delivery method is the most common, simple, and effective approach to cell editing. Using RNP minimizes immunological and toxic side effects, reduces off-target activity, , and achieves high editing efficiency . Additionally, RNP editing occurs rapidly, which prevents unintended genomic changes and ensures the method’s safety .…”
mentioning
confidence: 99%